Relasi Ilmu, Filsafat dan Agama Dalam Dimensi Filsafat Ilmu - Abu Tamrin (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2019)
Abstract:Philosophy is one of the fields of science that examines how to think deeply about something. Understanding of science comes from the Arabic words ‘science, English science, Dutch watenchap, and German wissenchap. Knowledge can be a science if it has special characteristics, arranged methodically, systematically, electronically (related) about a particular field and reality. Classification of science classification has developed according to its era. There are 5 truth theories according to Williams. Besides that there are positivistic, essentialistic, constructivist, and requistic theories. One field of philosophy is epistimologi often called the theory of knowledge. There are two theories of knowledge, namely realism and idealism. The method of gaining knowledge: empiricism, rationalism, phenomenalogical teachings of Khan. Methods in the theory of knowledge: Inductive, contemplative and dialectical. The next paper discusses religion which is an Indonesian term. Religion (English), religion (Dutch), and din (Arabic). There is a word between religion and life. In Islam there is a religion of heaven (samawi) or